Supportive-educative needs of patients with coronary heart disease: An investigation of clinical nurses - Aguscik Aguscik; Rahmad Aswin Juliansyah; Rosnani Rosnani; Devi Mediarti; Christina Yeni Kustanti; Bangun Mukti Ardi; Muhammad Kamil Che Hasan; Inbar Levkovich; Agus Setiawan; Hidayat Arifin (Jurnal Keperawatan Padjadjaran, 2024)
Background: The rising prevalence of coronary heart disease (CHD) has highlighted the need for supportive-educative efforts, particularly in nursing. These initiatives are crucial for improving self-care management in CHD patients, enhancing their quality of life. Clinical nurses are key in this role, leveraging their direct patient interaction and expertise to provide tailored education and support. Purpose: This study aimed to investigate the supportive-educative needs of CHD patients from the perspective of clinical nurses. Methods: A descriptive qualitative study was conducted for this research. Participants included 30 clinical nurses responsible for caring for CHD patients in both inpatient wards and outpatient polyclinics. Interview guidelines were utilized to collect data through in-depth interviews, triangulation, and the obtained interview data were analyzed using the thematic analysis approach.  Results: We identified four themes related to the supportive-educative needs of CHD patients: 1) engaging and informative media; 2) culturally sensitive approaches; 3) nurses’ attitudes; and 4) family empowerment. Conclusion: Supportive education, tailored to the needs of CHD patients, is vital for effective disease management. This study's findings highlight the importance of incorporating four key elements into supportive education: engaging and informative media to enhance learning, culturally sensitive approaches to address diverse patient needs, the positive impact of nurses’ empathetic attitudes, and the empowerment of families in the care process. Integrating these aspects can significantly aid CHD patients in developing self-care skills that positively influence their quality of life.